Glucocorticoid Therapy in Inflammatory Bowel Disease: Mechanisms and Clinical Practice - Bruscoli, Stefano; Febo, Marta; Riccardi, Carlo; Migliorati, Graziella (Frontiers in Immunology, 2021)
Inflammatory bowel disease (IBD) comprises ulcerative colitis (UC) and Crohn’s disease (CD). IBD etiopathology is multifactorial and involves alteration of immune cells and chronic activation of the inflammatory cascade against yet unknown environmental factors that trigger the disease. IBD therapy aims at improving the quality of life and reducing the risk of disease-related complications to avoid the need for surgery. There is no specific cure for IBDs, and the focus of therapy is supportive measures and use of anti-inflammatory and immunosuppressive drugs. Glucocorticoids (GCs) are powerful anti-inflammatory and immunomodulatory agents used to treat many acute and chronic inflammatory diseases. GCs remain basic treatment for moderate-to-severe IBD, but their use is limited by several important adverse drug effects. Topical administration of a second-generation of GCs, such as budesonide and beclomethasone dipropionate (BDP), represents a valid alternative to use of older, systemic GCs. Administration of second-generation GCs shows promisingly high topical activity and less systemic toxicity, but maintenance therapy with these new GCs in IBD patients is associated with multiple adverse effects. In this review, we make a comparative analysis of the efficacy of first-generation and second-generation GCs in IBD treatment. Unraveling GC biology at the molecular level to uncouple their clinical benefits from detrimental effects is important. One approach is to consider new GC mediators, such as glucocorticoid-induced leucine zipper, which may have similar anti-inflammatory properties, but avoids the side effects of GCs. This in-depth analysis can help to improve the development and the clinical outcomes of GC therapies in IBD.